Association of flame retardants, polybrominated diethyl ethers (PBDEs), with vitamin D in female subjects - Butler, Alexandra E.; Brennan, Edwina; Drage, Daniel S.; Sathyapalan, Thozhukat; Atkin, Stephen L. (Chemosphere (Oxford), 2023)
A class of flame retardants, polybrominated diethyl ethers (PBDEs), are known endocrine disrupters and may induce the hepatic enzymes CYP24 and CYP3A that promote 25-hydroxylation of vitamin D3. Therefore, this study examined the association of PBDEs with vitamin D3 (25(OH)D3) and the active 1,25-dihydrovitamin D3 (1,25(OH)2D3) in a cohort of non-obese women. 58 female participants (age:31.9 ± 4.6 years; body mass index (BMI):25.7 ± 3.7 kg/m2) had seven indicator PBDEs [PBDE28; PBDE47; PBDE99; PBDE100; PBDE153; PBDE154; PBDE183] measured using high resolution gas chromatography, with ƩPBDE level calculated. 25(OH)D3 and 1,25(OH)2D3 levels were determined by isotope-dilution liquid chromatography tandem mass spectrometry. Plasma level of calcium/calmodulin-dependent protein kinase type 1 (CaMK1) was measured by Somascan proteomics. In this cohort, vitamin D3 (25(OH)D3) and 1,25(OH)2D3 levels were 22.9 ± 11.2 ng/mL and 0.05 ± 0.02 ng/mL, respectively. Of those, 28 had vitamin D deficiency [25(OH)D3 level <20 ng/mL (<50 nmol/L)]. For the whole group, individual PBDEs (PBDE28; PBDE47; PBDE99; PBDE100; PBDE153; PBDE154; PBDE183) and ƩPBDEs did not correlate with 25(OH)D3 or its active metabolite 1,25(OH)2D3 nor with BMI. For the subset who were 25(OH)D3 sufficient, negative correlations were found for 1,25(OH)2D3 with PBDE153 (ρ = −0.77; p = 0.02) and PBDE100 (ρ = −0.72; p = 0.005). In the subset of women who were 25(OH)D3 deficient, positive correlations were found for 1,25(OH)2D3 with PBDE153 (ρ = 0.68; p = 0.02) and ƩPBDEs (ρ = 0.57; p = 0.03). Using sufficient and deficient subset categories, no correlations were seen with 25(OH)D3 nor any of the PBDEs, and PBDEs did not correlate to renal function (estimated glomerular filtration rate, eGFR). 1,25(OH)2D3 was negatively associated with CaMK1 (r = −0.36; p = 0.03) as was PBDE153 (r = −0.31; p = 0.02). PBDEs were not associated with 25(OH)D3, but PBDE100 and 153 correlated with its active 1,25(OH)2D3 metabolite and PBDE153 correlated to the calcium modulator CaMKI, suggesting that PBDE effects could either be mediated through vitamin D status or that functional inactivation or inhibition of 1,25(OH)2D3 may contribute to the impact of vitamin D deficiency. [Display omitted] •Polybrominated diethyl ethers (PBDEs), are known endocrine disrupters.•PBDEs may promote 25-hydroxylation of vitamin D3 by inducing CYP24 and CYP3A.•We examined the association of PBDEs with 25(OH)D3 and 1,25(OH)2D3 in women.•PBDE100&153 correlated to 1,25(OH)2D3; PBDE153 correlated to Ca2+-modulator CaMKI.•PBDE effects could be mediated via inactivation/inhibition of 1,25(OH)2D3.